PALEOMAGNETISM OF PERMIAN THROUGH EARLY TRIASSIC SEQUENCES IN CENTRAL SPITSBERGEN: IMPLICATIONS FOR PALEOGEOGRAPHY - Nawrocki J. (My University, 1999)
Upper Carboniferous through Lower Triassic sediments from Spitsbergen have yielded paleomagnetic results, with those for the Late Gzhelian-Early Permian being the more reliable. The corresponding pole (38°N, 171°E) is fully concordant with the Early Permian segment of the apparent polar wander path for Baltica. It does not support hypotheses about post-Carboniferous mobilism of Spitsbergen with respect to Stable Europe. Neither Mesozoic nor later rifting processes changed the position of Spitsbergen considerably in relation to the Stable Europe.
Keywords: SPITSBERGEN; PALEOMAGNETISM; PERMIAN; APPARENT POLAR WANDERING; PALEOGEOGRAPHY; Paleozoic::Permian; Палеозой::Пермская